LEGAL CONTEXT OF THE LAND RESOURCES PRIVATIOZATION IN UZBEKISTAN - Abdumannabova Muyassarxon Abdurashid qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
INTRODUCTION Land relations occupy a special place in the legal system of any state, and this is particularly  true  for  the  Republic  of  Uzbekistan,  where  land  has  historically  been treated not as an ordinary object of civil turnover but as “national wealth” subject to direct state control. For more than seven decades under the Soviet system, and for nearly three further decades of post-independence development, land in Uzbekistan remained  the  exclusive  property  of  the  state.  The  privatization  of  land  resources emerged as one of the most legally and politically sensitive undertakings. Unlike the privatization  of  industrial  enterprises  or  housing  stock,  which  had  already  been substantially completed by the late 1990s, the transfer of land into private ownership required  not  only  ordinary  legislative  amendment  but,  ultimately,  a  change  to  the constitutional order itself. The  protection  of  land  resources  and  their  rational  use  constitute  one  of  the principal directions of state environmental policy. As an integral component of the ecological system, land resources play a vital role in ensuring the stability of the natural environment,  as  well  as  in  strengthening  the  material  foundation  of  the  state sovereignty and economic potential of the Republic of Uzbekistan.